Influencing factors among rural households on their awareness level about mosquito borne diseases-a descriptive cross-sectional study from endemic area in Kerala - P., Thiyagarajan; N., Piramanayagam (International Journal Of Community Medicine And Public Health, 2020)
Background: The global burden of vector borne diseases (VBDs) is 17% of all infectious diseases. Health systems in many tropical and subtropical countries are overwhelmed by outbreaks of dengue, malaria, chikungunya with highest burden among poorest populations. India carries 85% of the global malaria burden. WHO-Global vector control response identified behavioural change need and initiated education to improve public awareness. Malaria, filariasis, chikungunya, JE, dengue is currently endemic in rural Kerala. Main objective of this study was to assess the awareness level in general about the mosquito borne diseases (MBDs) among households from rural field practice areas and to find out its association between influencing factors. Methods: A descriptive cross-sectional study conducted by household survey in 2019 in Perumatty panchayat of rural Kerala. Participants were interviewed separately. The mixed pattern questionnaire consisted of dichotomized and multiple answer questions with scoring and interpretations to assess the awareness level in general. The final outcome was categorized as good, partial and poor awareness and analysed for frequencies and associations. Results: More participants were in 31-45 years age group (39.5%) with mean age 43.5±13.6. Only 7% good, 70% partial and 20% poor awareness levels were found. 32.9% participants had completed secondary school. 43.9% belong to middle class family. 75% participants were aware on ‘mosquito bite’ as mode of transmission. 14.3% aware on all major symptoms. Education, family history, SEC and Knowledge source had significant influence between awareness categories. Conclusions: Low awareness level on MBDs among the rural population needs proper health education interventions.